Letalidade E Sub-Letalidade De Acaricidas Utilizados Na Cultura Do Coqueiro Sobre Amblyseius largoensis (Muma) (Acari: Phytoseiidae) - Barros, Maria Edvânia Neves (2021)
The mite Amblyseius largoensis Muma has been cited as an important biological control agent for the pest mite Raoiella indica Hirst. Since A. largoensis is not commercially available, coconut producers have used products registered for another pest mite in coconut (Aceria guerreronis Keifer) in order to minimize the losses caused by R. indica. However, the effect of such products on populations of A. largoensis, which naturally occur in coconut leaflets infested with R. indica, is not known. The natural contribution (predation) of this predator can be explored through control strategies that allow its conservation, highlighting, in this sense, the need to use selective products. The present study aimed to evaluate the effect of registered acaricides for coconut (azadiractin, abamectin, chlorfenapyr and fenpyroximate) on survival, consumption, oviposition, efficiency of food conversion into eggs and on the functional and numerical responses of the predatory mite A. largoensis. The acaricides abamectin, fenpyroximate and chlorfenapyr reduced the survival of females of A. largoensis. Abamectin was the only acaricide to affect predation, oviposition and food conversion efficiency of A. largoensis. Amblyseius largoensis exhibited a type II functional response when fed with R. indica eggs, and the type of functional response was not altered by exposure to acaricides. Despite not altering the type of functional response, exposure to abamectin resulted in a decrease in the average number of prey consumed by the predator. Exposure to acaricides increased prey handling time by 67%, 25%, 38% and 35% for abamectin, azadirachtin, fenpyroximate and chlorfenapyr, respectively. Exposure to abamectin reduced the attack rate by 52%. The numerical response was affected only by exposure to abamectin, where only 60% of the females performed oviposition and, regardless of the density of prey offered, the average number of eggs/female/day was always lower than 0.36. The efficiency of food conversion into egg biomass decreased with increasing prey densities, and this trend was not altered by exposure to acaricides. Despite not altering the trend of efficiency of conversion of food into egg biomass, exposure to abamectin drastically compromised the oviposition of A. largoensis, not being observed an increase in egg production with increasing prey density.